(untitled) - Usunier, Jean-Claude (London, 1996)
The cultural variable of international marketing is of prime importance in that it impacts communication, business negotiation, consumer needs and attitudes, and the design and implementation of marketing strategies. This book compares national marketing systems and local commercial customs in various countries, emphasizing what is country-specific and what is universal. Covers selling, negotiation, and marketing communications, with new chapters on cross-cultu ral consumer behavior and the cultural aspects of regional integration. For export marketing managers, as well as anyone involved in marketing activities with culturally different markets.
Keywords: Tiếp thị xuất khẩu,Export marketing; Khía cạnh xã hội,Social aspects